Inclusive leadership and employees' knowledge hiding behaviors: The mediating role of interpersonal trust and affective commitment as a moderator - Ahmed Salman Abbasi; Zaki Rashidi; Usman Ghani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Grounded in Social Learning Theory, this study explores the connection between Inclusive Leadership and Knowledge Hiding Behavior, to better understand the mechanism that how inclusive leadership influences knowledge hiding, and reasons behind certain individuals; dissimilar to others; are comparatively less probable to involve in knowledge hiding under inclusive leadership. This study proposes that Interpersonal trust mediates, and, Affective Commitment moderates the relationship between inclusive leadership, versus knowledge hiding. Data were collected from 297 employees through questionnaire currently enrolled in MBA program in a large private sector university of Pakistan. Confirmatory factor analysis and Process Macro were used to ascertain the reliabilities, validities and hypothesized model through SPSS 22.0 and AMOS 22.0. The findings tell us that inclusive leadership negatively and significantly influences knowledge hiding. Further, the findings exhibit thar interpersonal trust mediates, and, affective commitment, reveals a moderating connection between inclusive leadership, and knowledge hiding. This could be considered one of the pioneer studies which tend to contribute to the literature of knowledge hiding and leadership, by strengthening association between inclusive leadership and knowledge hiding behaviors, converging on the mechanism and boundaries of the relationship.
Keywords: 330; Inclusive leadership; knowledge hiding; affective commitment; interpersonal trust; Pakistan